Sequential Vaccination With Heterologous Acinetobacter baumannii Strains Induces Broadly Reactive Antibody Responses - Kamuyu, Gathoni; Suen Cheng, Yat; Willcocks, Sam; Kewcharoenwong, Chidchamai; Kiratisin, Pattarachai; Taylor, Peter W.; Wren, Brendan W.; Lertmemongkolchai, Ganjana; Stabler, Richard A.; Brown, Jeremy (Frontiers in Immunology, 2021)
Antibody therapy may be an alternative treatment option for infections caused by the multi-drug resistant (MDR) bacterium Acinetobacter baumannii. As A. baumannii has multiple capsular serotypes, a universal antibody therapy would need to target conserved protein antigens rather than the capsular polysaccharides. We have immunized mice with single or multiple A. baumannii strains to induce antibody responses to protein antigens, and then assessed whether these responses provide cross-protection against a collection of genetically diverse clinical A. baumannii isolates. Immunized mice developed antibody responses to multiple protein antigens. Flow cytometry IgG binding assays and immunoblots demonstrated improved recognition of both homologous and heterologous clinical strains in sera from mice immunized with multiple strains compared to a single strain. The capsule partially inhibited bacterial recognition by IgG and the promotion of phagocytosis by human neutrophils. However, after immunization with multiple strains, serum antibodies to protein antigens promoted neutrophil phagocytosis of heterologous A. baumannii strains. In an infection model, mice immunized with multiple strains had lower bacterial counts in the spleen and liver following challenge with a heterologous strain. These data demonstrate that antibodies targeting protein antigens can improve immune recognition and protection against diverse A. baumannii strains, providing support for their use as an antibody therapy.